The Many Faces of Panentheism: An Editorial Introduction - Atmanspacher, Harald (Zygon, 2017)
A well-known difficulty of the interdisciplinary dialogue beyond the limits of particular disciplines is the lack of common ground regarding their metaphysical and methodological assumptions and commitments. This is particularly evident for the precarious relationship between science and religion. In a 2016 conference entitled The Many Faces of Panentheism held in Zurich, and now in this introduction as well as this section, we try to counteract this situation by choosing a focus theme located at the interface between nature and the divine. Thus, key perspectives, arguments, and implications of panentheism are introduced not only from one selected point of view but in relation to others. This allows us to explore territory beyond the boundaries of disciplinary backgrounds and to address intellectual and practical consequences for current debates.